2012
DOI: 10.2174/138955712802762149
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Reproductive Effect of Sex Steroids: Their Role During Immunity to Helminth Parasite Infections

Abstract: During the helminth infections, the immune system tends to be modulated by host's sex hormones. Actually, many studies show the reciprocal relationship between sex steroids, the immune system and the elimination or establishment of helminth parasites. Is well known that innate immune response determines the type of adaptive immune response, so the effects in the innate immune response by hormones may affect subsequent adaptive immunity. The sex steroids as estrogens, progesterone and testosterone regulate grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…All mice were handled at room temperature for 14 days before treatment, and all mice were age-matched (12 weeks old). We used only male C57BL/6 N mice for this primary study because gender of mice affects hormones and cell-mediated immune response [ 20 , 21 ]. Cytokine expression also differs between male and female mice [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…All mice were handled at room temperature for 14 days before treatment, and all mice were age-matched (12 weeks old). We used only male C57BL/6 N mice for this primary study because gender of mice affects hormones and cell-mediated immune response [ 20 , 21 ]. Cytokine expression also differs between male and female mice [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…These research efforts may disclose important links between steroid hormones and the immune system, thereby offering chances for novel therapeutic options. Several clinical and experimental studies demonstrated significant effects of sex hormones on cell mediated immune responses 5 , 6 . With respect to humoral immune responses, a remarkable preponderance of females are susceptible to autoimmune diseases, i.e., systemic lupus erythematosus (SLE), Hashimoto thyroiditis, rheumatoid arthritis, and primary biliary cirrhosis 7 - 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that the severity of malaria infection differs between males and females [75], with men developing more severe parasitaemia and pathology than women [76]. In addition, it has been described that in general women produce more intense humoral and cell-mediated immune responses than males [77, 78]. However, no effect of sex was observed on the analyte concentrations in either infected or uninfected subjects, although a sex interaction was found with year for TNF, IFN-γ, IL-4, RANTES and GM-CSF, the impact of which is difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%